Prognostic role of renal replacement therapy among hospitalized patients with heart failure in the Brazilian national public health system - Coy-Canguçu, Andréa; Antunes-Correa, Lígia M.; Mazzali, Marilda; Abrão, Paula; Ronco, Fernanda; Teixeira, Cinthia Montenegro; Viana, Karynna Pimentel; Cordeiro, Guilherme; Longato, Mauricio; Coelho, Otávio Rizzi; Matos-Souza, José Roberto; Nadruz, Wilson; et al. (Frontiers in Cardiovascular Medicine, 2023)
Introduction Data on patients hospitalized with acute heart failure in Brazil scarce. Methods We performed a cross-sectional, retrospective, records-based study using data retrieved from a large public database of heart failure admissions to any hospital from the Brazilian National Public Health System (SUS) (SUS Hospital Information System [SIHSUS] registry) to determine the in-hospital all-cause mortality rate, in-hospital renal replacement therapy rate and its association with outcome. Results In total, 910,128 hospitalizations due to heart failure were identified in the SIHSUS registry between April 2017 and August 2021, of which 106,383 (11.7%) resulted in in-hospital death. Renal replacement therapy (required by 8,179 non-survivors [7.7%] and 11,496 survivors [1.4%, p < 0.001]) was associated with a 56% increase in the risk of death in the univariate regression model (HR 1.56, 95% CI 1.52 -1.59), a more than threefold increase of the duration of hospitalization, and a 45% or greater increase of cost per day. All forms of renal replacement therapy remained independently associated with in-hospital mortality in multivariable analysis (intermittent hemodialysis: HR 1.64, 95% CI 1.60 -1.69; continuous hemodialysis: HR 1.52, 95% CI 1.42 -1.63; peritoneal dialysis: HR 1.47, 95% CI 1.20 -1.88). Discussion The in-hospital mortality rate of 11.7% observed among patients with acute heart failure admitted to Brazilian public hospitals was alarmingly high, exceeding that of patients admitted to North American and European institutions. This is the first report to quantify the rate of renal replacement therapy in patients hospitalized with acute heart failure in Brazil.